PALLIATIVE SURGERY FOR INTESTINAL OBSTRUCTION DUE TO RECURRENT OVARIAN CANCER - Parveen, Zahida; Qureshi, Ahmad Nadeem; Akbar, Mohammad; Zafar, Arshad; Subhani, Aqeel (Journal of Ayub Medical College Abbottabad, 2008)
Background: Intestinal Obstruction is a frequent complication after operation for Ovarian Cancer. This study was done to see the outcome of palliative surgery for Intestinal Obstruction due to recurrent ovarian Cancer. Methods: We retrospectively evaluated the records of all the patients who presented with intestinal obstruction after operations for Ovarian Cancer in all the three Surgical Units of Ayub Teaching Hospital Abbottabad from March 1998 to April, 2009. Demographic data, type of management, morbidity, mortality, hospital stay, surgical procedure, symptomatic relief, return of bowel function and outcome were analyzed. Results: There were 56 patients with symptoms of partial or complete intestinal obstruction. Conservative treatment was successful in 22 (39%) patients. Laparotomy was done in 30 (53.5%) patients. The cause of intestinal obstruction was adhesions 8 (26.6%), local recurrence 10 (33.3%) and diffuse carcinomatosis in 12 (40%) patients. Palliative surgery was done in 20 (66.6%) patients while 8 (26.6%) had adhesionolysis only. 9 (30%) patients had resection and anastomosis, 7 (23.3%) had bypass surgery, 3 (10%) had colostomy and one (3%) had Hartmann procedure. Postoperative complications occurred in 26 (86.6%) patients. 12 (40 %) patients died after surgery. Mean hospital stay was 18 (9-42) days. Palliative surgery was successful in 8 (26.65%). Conclusions: Majority of patients with Intestinal obstruction after operation for Ovarian Cancer can be managed conservatively. Palliative surgery is associated with high mortality and morbidity but it should be done in patients not responding to conservative measures. Keywords: Ovarian cancer, Intestinal Obstruction, Laparotomy